The Effect Of Work-Life Balance And Quality Of Work Life On Employee Performance With Gender As A Moderating Variable - Cynthia Aulia Kurniasari; Yustina Erti Pravitasmara Dewi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Work-life balance and quality of work life are two ways to maintain good employee performance, which simultaneously result to meeting company goals. This present study aims to investigate the effect of work-life balance and quality of work life on employee performance with gender as a mediating variable. This study was done in a quantitative manner using explanatory research approach. This study examined employees from PT XYZ – one of multi-finance companies in Central Java. The data was collected by distributing questionnaires and then analyzed using moderated regression analysis (MRA). The results confirm that both work-life balance and quality of work life have a positive effect on the employee performance in PT XYZ. Further, the gender is also proven to moderate the effect of both work-life balance and quality of work life on the employee performance in PT XYZ. The use of gender as the mediating variable in this study contribute to the work-life balance literature, which makes it a differentiating factor from previous researches. The results of this study imply practical benefits for the employers in making decisions for their employees in efforts to achieve the work-life balance.